ANALISIS TENTANG PENYELENGGARAAN BADAN USAHA MILIK DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA SEKELADI HILIR KEC. TANAH PUTIH KAB. ROKAN HILIR - Rudi . Adi (Universitas Islam Negeri sultan syarif kasim Riau, 2020)
Abstract : The birth of an autonomy system or decentralization bring new spirit in realizing the national ideals of the Indonesian nation. Development initially focused on the central region, then shifts to development that starts from the regions equally The birth of Law No.23 Th.2014 is proof that the autonomy system really wants to be perfected, although in its development it does not provide change. Therefore, Law No.6 Th.2014 on Villages was born, which then becomes a new round of national development starting from the village. The One form of development regulated in the Act is establish BUMDes with the aim that villages become part of the national development process. This study discusses how the formation and organization of village-owned enterprises in improving the welfare of the community in the Sekeladi Hilir village and Tanah Putih sub-district and Rohil districts. This research is a qualitative research model with the problem approach method that is an empirical juridical approach method. Next, data collection technique is to collect library materials (secondary data), and data collection through field observations and interviews with informants who have been determined by Purpossive Sampling techniques (primary data). The Implementing BUMdes in Sekeladi Hilir Village, there are a number of problems that occur. The First, the formation of BUMDes is not well analyzed it can be seen from BUMdes managers who are not professional in managing BUMDes. Second, the type of BUMDes business established was a gas cylinder business, it is considered to have paid less attention to the potential of the village as well as opportunities in adding PADes in Sekeladi Hilir Village. Third, since the establishment of BUMdes in the downstream village in 2015 until today it has not made any changes to the income of the village and the welfare of the downstream village communities.Keywords : Autonomy System, Village-Owned Enterprises/BUMDes, Village Community Welfare Abstrak : Lahirnya system otonomi atau desentralisasi membawa semangat baru dalam mewujudkan cita-cita nasional bangsa Indonesia. Pembangunan yang awalnya terfokus pada wilayah pusat lalu bergeser pada pembangunan yang dimulai dari daerah-daerah secara merata. Lahirnya UU No.23 Th.2014 adalah bukti bahwa system otonomi benar-benar ingin disempurnakan, meskipun pada perkembangannya kurang memberikan perubahan. Oleh karena itu, lahirlah UU No.6 Th.2014 Tentang Desa, yang kemudian menjadi babak baru pembangunan nasional yang dimulai dari desa. Salah satu bentuk pembangunan yang diatur dalam UU tersebut adalah mendirikan BUMDes dengan tujuan agar desa menjadi bagian dari proses pembangunan nasional. Penelitian ini membahas tentang bagaimana pembentukan dan penyelenggaraan badan usaha milik desa dalam meningkatkan kesejahteraan masyarakat di desa sekeladi hilir kec. tanah putih kab. rokan hilir. Penelitian ini merupakan model penelitian kualitatif dengan metode Pendekatan masalah yaitu metode pendekatan yuridis empiris. Selanjutnya, Teknik pengumpulan data yaitu dengan mengumpulkan bahan-bahan kepustakan (data sekunder), serta pengumpulan data melalui Observasi lapangan dan wawancara dengan Informan yang telah ditentukan dengan teknik Purpossive Sampling (data primer). Dalam penyelenggaraan BUMdes di Desa Sekeladi Hilir, terdapat beberapa masalah yang terjadi. Pertama, pembentukan BUMDes tidak dianalisa dengan baik hal itu terlihat dari pengelola BUMdes yang tidak professional dalam mengelola BUMDes. Kedua, Jenis Usaha BUMDes yang didirikan adalah usaha tabung gas, hal itu dinilai kurang memperhatikan potensi desa serta peluang dalam menambahkan PADes. Ketiga, sejak berdirinya BUMdes di desa sekeladi hilir pada tahun 2015 sampai hari ini belum memberikan perubahan apapun bagi pendapatan desa dan kesejahteraan masyarakat desa sekeladi hilir.Kata Kunci: Sistem Otonomi, BUMDes, Kesejahteraan Masyarakat Desa,